“Efecto de la combinación de fosfito potásico con ácidos húmicos y fúlvicos, sobre el rendimiento del cultivo de arroz (Oryza sativa L.) de secano”. - Tapia Piedra, Manuel Stalin (2019)
IX. SUMMARY The present research work was carried out in the land of the "La Industria" farm, belonging to Mr. Carlos Torres Briones, located at Km. 2,0 of the Santa Lucia - Palestina highway. This experimental zone has a humid tropical climate, with average annual temperature of 25 ° C, annual precipitation of 1 200 mm, relative humidity of 50 % and height of 10 m.s.n.m. The rice variety SFL-09 will be used as the sowing material. The treatments consisted of Naturfos in doses of 0,5 and 1,0 L/ha; Naturvital - plus in doses of 0,5 and 1,0 L/ha; the combination of Naturfos + Naturvital - plus in doses of 0,5 + 0,5 L/ha, 0,5 + 1,0 L/ha, 1,0 + 0,5 L/ha, 1,0 + 1,0 L/ha; Evergreen 1,0 L/ha and control without application of products. We used the experimental design of blocks at random with ten treatments and three repetitions, for the evaluation and comparison of means of the treatments, we used the Tukey test at 95%. For the execution of the test, all the agricultural tasks that the crop requires for its normal development were performed, such as Land Preparation, Sowing, Weed Control, Phytosanitary Control, Fertilization, Irrigation and Harvesting. Based on the results obtained, it was determined that the combinations of potassium phosphite with humic and fulvic acids did not obtain the highest yields in rice cultivation; the control treatment without application of products flourished in a longer time, while the Evergreen treatment 1 L/ha matured in a longer time; the agronomic characteristics of plant height, panicle length, number of tillers and panicles/m2, number of grains per panicle, grain-straw ratio and weight of 1000 grains reached better results with the application of Evergreen, in doses of 1,0 L/ha at 20 and 40 days after the transplant and when applying Evergreen, in a dose of 1,0 L/ha, the highest crop yield was reached with 7541,7 kg/ha and net profit of $ 941,14/ha . Keywords: rice, yield, humic acids, fulvic acids.